Data analysis with stata:/ Explore the big data field and learn how to perform data analytics and predictive modelling in stata - Kothari, Prasad (Birmingham Packt Publishing Ltd, 2015)
This book covers data management, graphic visualization, and programming in Stata. Starting with an introduction to Stata and data analysis, you will move on to Stata programming and data management. The book takes you through data visualization and all the important statistical tests in Stata. Linear and logistic regression in Stata is also covered.
Includes index
osa 10/01/2019, ijb,28/01/2019
Loans
Keywords: Stata; Quantitative research; Big data; Integrated software